Emergency care of children and young people - Cleaver, Karen, 1959-; Webb, Janet, 1961- (Blackwell Pub., 2007)
Children and young people account for a quarter of all patients treated in emergency departments in the UK, with three million children attending emergency departments every year. Emergency Care of Children and Young People prepares practitioners for the challenges of caring for children in emergency departments. Children requiring emergency care have unique and differing needs and may not respond or cooperate during an initial assessment as an adult would. Emergency Care of Children and Young People is an essential reference for all health care professionals working with children in the emerg.